A felelősség társadalma - Szilágyi, Tamás (Kultúratudományi Szemle, 2022)
The society of responsibility Tamás Szilágyi The concept of ’responsibility’ is a relatively recent one in philosophy and the social sciences, so its definitional framework is rather vague. In some cases, the concept denotes different meanings, depending on whether it is used in legal terminology or in a contemporary environmental ethical context. This paper examines the evolution of the concept of responsibility in Western culture, how the meaning of responsibility has changed over two centuries, how it has been transformed in the works of thinkers such as Hans Jonas, Richard McKeon or Amitai Etzioni. The main question is: beyond the organisational framework, how does responsibility appear in society or at the level of the individual? Does the understanding of responsibility move away from human-human relations towards human-environment relations and make nature the object of human responsibility? Will the 'society of burnout' (Müdigkeitsgesellschaft) really be able to transform itself into a ’society of responsibility’ (Verantwortungsgesellschaft)?